Sexual communication among intercultural couples with a Finnish partner - Schmit, Baylei (2016)
In this study the topic of sexual communication, satisfaction, and accommodation in intercultural relationships is examined. Intercultural couples are in need of more attention in scholarly research, especially on the topic of sexual communication. This study aims to bring the topic into clear view. One research question leads this study in asking: “what factors play a role in how intercultural couples discuss sex?” 18 participants, making up 9 couples, were interviewed separately about their sexual communication; following the interviews each couple completed a survey together on the same topic. The Communication Accommodation Theory is utilized to evaluate how accommodative intercultural couples are while discussing sex with one another. The findings from this research highlight 3 main factors which play a role in how intercultural couples discuss sex: open communication, cultural differences, and speaking English.